Pembelajaran Berbicara Berbantuan Komik Strip untuk Pembelajar BIPA Korea Selatan - Aswan Aswan (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
Speaking skill is a very complex skill because it involves other skills. Especially in BIPA learning, relevant strategies are needed as an alternative to learn BIPA. Therefore, this study is intended to describe the results of learning process by using comic strip toward speaking practice. Based on the tracing of previous studies, it was not found any research related to the use of comic strips in learning to speak BIPA. The method used in this research is qualitative. The participants in this study were South Korean BIPA learners in intermediate levels of ability. The results of the data analysis show that learning to speak using comic strip can be an alternative in teaching BIPA. This can be seen in all activities which run effectively. In addition, learners also give very positive responses during learning